2022
DOI: 10.4041/kjod.2022.52.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of facial asymmetry phenotypes in adult patients with skeletal Class III malocclusion using three-dimensional computed tomography and cluster analysis

Abstract: Objective To classify facial asymmetry (FA) phenotypes in adult patients with skeletal Class III (C-III) malocclusion. Methods A total of 120 C-III patients who underwent orthognathic surgery (OGS) and whose three-dimensional computed tomography images were taken one month prior to OGS were evaluated. Thirty hard tissue landmarks were identified. After measurement of 22 variables, including cant (°, mm), shift (mm), and yaw (°) of the maxilla, maxillary dentition (Max-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 28 publications
2
16
1
Order By: Relevance
“…Researchers attributed the etiology of the Class III malocclusion to morphologic or positional disharmony between the maxilla and the mandible during the growth period [ 4 ]. Since there are many variations in Class III morphology, it became a necessity to use the wide applications of 3D imaging in orthodontics to study the volumes of the jaws for a better understanding of the problem [ 5 8 ] that may lead to more accurate treatment techniques [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers attributed the etiology of the Class III malocclusion to morphologic or positional disharmony between the maxilla and the mandible during the growth period [ 4 ]. Since there are many variations in Class III morphology, it became a necessity to use the wide applications of 3D imaging in orthodontics to study the volumes of the jaws for a better understanding of the problem [ 5 8 ] that may lead to more accurate treatment techniques [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 3D facial scan images cannot evaluate asymmetry in the hard tissue. Although PA cephalogram has inevitable errors by the 2-dimensional analysis of a 3D object, 5 it is useful for the initial screening of FA.…”
Section: Discussionmentioning
confidence: 99%
“…11 The onset of a mandibular asymmetry in patients affected by prognathism has been also associated with the increased volume of the ipsilateral cranial base, or with lengthening of the ramus and/or of the mandibular body with respect to non-asymmetric patients 8,17 The interest for the asymmetric class III malocclusion has greatly increased in the last years, and Ha et al reported that two-thirds of class III patients who underwent orthognathic surgery were affected by some degree of facial asymmetry. 11,12,14,[18][19][20] In this malocclusion pattern, maxillary yaw develops as a gradual dental compensation, in the attempt to find the best dental intercuspation which may ensure function; especially in age of growth, the dental characteristics of the occlusion (missing teeth, premature contacts, cross bites, etc.) may affect the severity an asymmetric pattern of growth that may affect occlusion and create multiple dental compensations, if not corrected.…”
Section: Discussionmentioning
confidence: 99%
“…7 The use of cone beam computed tomography (CBCT) in threedimensional diagnosis is boosting the radiographic characterization of different types of facial asymmetry, and the protocols to measure the transverse rotation of the maxillo-facial complex are becoming fast and simple. 7,[11][12][13][14] In this study, we have tested a cephalometric method to assess the yaw on a CBCT three-dimensional reconstructed image of the skull, by evaluating the amount of the maxillary skeletal and dental yawing compensations in two groups of patients clinically affected by a similar malocclusion, a class III with deviation of the lower midline. The aim of the statistical analysis was to compare the measurements of the rotating side with respect to the healthy one in each group, and to analyse if two aetiologically different types of facial asymmetry could significantly affect the transverse maxillary rotation.…”
Section: Introductionmentioning
confidence: 99%